2009
DOI: 10.19173/irrodl.v10i2.596
|View full text |Cite
|
Sign up to set email alerts
|

Looking under the Bonnet: Factors Affecting Student Adoption of E-Learning Systems in Jordan

Abstract: The primary questions addressed in this paper are the following: what are the factors that affect students" adoption of an e-learning system and what are the relationships among these factors?This paper investigates and identifies some of the major factors affecting students" adoption of an e-learning system in a university in Jordan. E-learning adoption is approached from the information systems acceptance point of view. This suggests that a prior condition for learning effectively using e-learning systems is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
207
9
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(277 citation statements)
references
References 42 publications
(32 reference statements)
28
207
9
9
Order By: Relevance
“…The concept of self-efficacy can be defined as a person's perception of their ability to perform particular behaviors such as the capacity to undertake successfully certain tasks (Abbad et al, 2009). Indeed prior research in relation to computer self-efficacy has indicated computer self-efficacy plays a crucial role in understanding an individual's information and communication technology acceptance (e.g.…”
Section: Self-efficacymentioning
confidence: 99%
“…The concept of self-efficacy can be defined as a person's perception of their ability to perform particular behaviors such as the capacity to undertake successfully certain tasks (Abbad et al, 2009). Indeed prior research in relation to computer self-efficacy has indicated computer self-efficacy plays a crucial role in understanding an individual's information and communication technology acceptance (e.g.…”
Section: Self-efficacymentioning
confidence: 99%
“…Se incluyó este constructo en la investigación considerando que el aspecto que evalúa, coincide con el comportamiento latinoamericano y en especial de Ecuador. Estudios previos antes analizaron este factor como importante (Abbad, Morris & de Nahlik, 2009;Chou & Tseng, 2011;Udzlmd, Bachtiar, Rachmadi & Pradana, 2014).…”
Section: La Influencia Socialunclassified
“…La disponibilidad de apoyo técnico es uno de los factores importantes en la determinación de la aceptación de la tecnología para la enseñanza (Abbad et al, 2009), especialmente en la etapa de inicio de la adopción de la tecnología. Lo expuesto coincide con los resultados de varios estudios (AlQudah Ahmed, 2014;Arteaga & Duarte, 2010;Ngai, Poon & Chan, 2007;Ramirez-Anormaliza, Sabaté & Guevara-Viejo, 2015).…”
Section: Soporte Técnicounclassified
See 2 more Smart Citations